2018
DOI: 10.1186/s12936-018-2402-6
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysis and haem oxygenase-1 induction during persistent “asymptomatic” malaria infection in Burkinabé children

Abstract: BackgroundThe haemolysis associated with clinical episodes of malaria results in the liberation of haem, which activates the enzyme haem oxygenase-1 (HO-1). HO-1 has been shown to reduce neutrophil function and increase susceptibility to invasive bacterial disease. However, the majority of community-associated malaria infections are subclinical, often termed “asymptomatic” and the consequences of low-grade haemolysis during subclinical malaria infection are unknown.Study design and resultsAs part of an ongoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 46 publications
3
21
2
Order By: Relevance
“…One hypothesis, therefore, is that malaria‐induced neutrophil dysfunction results from hemolysis‐ and IL‐10‐driven HO‐1 induction. In support of this hypothesis, in a recent study of persistent malaria infections, we have found that heme drives inflammation, that parasite density and inflammation then drives IL‐10 production, and that heme and IL‐10 both then induce HO‐1 …”
Section: The Role Of Il‐10 In Malaria Nts Coinfectionsupporting
confidence: 52%
See 3 more Smart Citations
“…One hypothesis, therefore, is that malaria‐induced neutrophil dysfunction results from hemolysis‐ and IL‐10‐driven HO‐1 induction. In support of this hypothesis, in a recent study of persistent malaria infections, we have found that heme drives inflammation, that parasite density and inflammation then drives IL‐10 production, and that heme and IL‐10 both then induce HO‐1 …”
Section: The Role Of Il‐10 In Malaria Nts Coinfectionsupporting
confidence: 52%
“…However, the majority of malaria infections in the world are asymptomatic, with chronic, low‐density infections . As recent and low‐density malaria infections are a risk factor for NTS bacteremia, it is also important to understand if hemolysis, and resulting induction of HO‐1 and IL‐10, seen during these “asymptomatic” infections reaches the threshold needed for neutrophil dysfunction. In other words, in addition to defining the pathways leading to neutrophil dysfunction, we also need to identify the point at which the balance tips from these being host protective to increasing the risk to invasive NTS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have characterized some of the underlying mechanisms by which Plasmodium infections increase susceptibility to invasive NTS infection (Cunnington et al, 2011(Cunnington et al, , 2012Lokken et al, 2014Lokken et al, , 2018Mooney et al, 2014Mooney et al, , 2018. First, Plasmodium-induced hemolysis results in the activation of heme oxygense-1 (HO-1), which mobilizes functionally immature granulocytes from the bone marrow.…”
Section: Introductionmentioning
confidence: 99%